Blockade of LAG-3 in PD-L1-Deficient Mice Enhances Clearance of Blood Stage Malaria Independent of Humoral Responses - Furtado, Raquel; Chorro, Laurent; Zimmerman, Natalie; Guillen, Erik; Spaulding, Emily; Chin, Shu Shien; Daily, Johanna P.; Lauvau, Grégoire (Frontiers in Immunology, 2021)
T cells expressing high levels of inhibitory receptors such as PD-1 and LAG-3 are a hallmark of chronic infections and cancer. Checkpoint blockade therapies targeting these receptors have been largely validated as promising strategies to restore exhausted T cell functions and clearance of chronic infections and tumors. The inability to develop long-term natural immunity in malaria-infected patients has been proposed to be at least partially accounted for by sustained expression of high levels of inhibitory receptors on T and B lymphocytes. While blockade or lack of PD-1/PD-L1 and/or LAG-3 was reported to promote better clearance of Plasmodium parasites in various mouse models, how exactly these pathways contributes to protection is not known. Herein, using the mouse model of non-lethal P. yoelii (Py) infection, we reveal that the kinetics of blood parasitemia as well as CD4+ T follicular helper (TFH) and germinal center (GC) B cell responses are indistinguishable between PD-1-/-, PD-L1-/- and WT mice. Yet we also report that monoclonal antibody (mAb) blockade of LAG-3 in PD-L1-/- mice promote accelerated control of blood parasite growth and clearance, consistent with prior therapeutic blockade experiments. However, neither CD4+ TFH and GC B cell responses, nor parasite-specific Ab serum titers and capacity to transfer protection differed. We also found that i) the majority of LAG-3+ cells are T cells, ii) selective depletion of CD4+ but not CD8+ T cells prevents anti-LAG-3-mediated protection, and iii) production of effector cytokines by CD4+ T cells is increased in anti-LAG-3-treated versus control mice. Thus, taken together, these results are consistent with a model in which disruption of PD-L1 and LAG-3 on parasite-specific CD4+ T cells unleashes their ability to effectively clear blood parasites, independently from humoral responses.